Fungsi Naratif Dongeng dalam Cerpen “Lu’lu’atu Ash-Shabāḥi” Karya Kamil Kailani - Khotimah, Husnul; Surur, Misbahus; Mustofa, Arif (Universitas Al Azhar Indonesia, 2025)
In oral societies, the tradition of story telling has never truly disappeared. In modern times, folktales can be presented in the form of short stories. As a genre of prose, short stories possess their own distinct characteristics. Moreover, they often embed historical narratives, adventure tales, and heroic stories, which are typically presented through various engaging plot structures. One example of an Arabic short story rich in folktale elements is